High-Throughput Fluorescence Polarization Assay to Identify Ligands Using Purified G Protein-Coupled Receptor. (October 2019) - Heine, P.; Witt, G.; Gilardi, A.; Gribbon, P.; Kummer, L.; Plückthun, Andreas
The development of cell-free high-throughput (HT) methods to screen and select novel lead compounds remains one of the key challenges in G protein-coupled receptor (GPCR) drug discovery. Mutational approaches have allowed the stabilization of GPCRs in a purified and ligand-free state. The increased intramolecular stability overcomes two major drawbacks for usage in in vitro screening, the low receptor density on cells and the low stability in micelles. Here, an HT fluorescence polarization (FP) assay for the neurotensin receptor type 1 (NTS1) was developed. The assay operates in a 384-well format and is tolerant to DMSO. From a library screen of 1272 compounds, 12 ( 1%) were identified as primary hits. These compounds were validated in orthogonal assay formats using surface plasmon resonance (SPR), which confirmed binding of seven compounds (0.6%). One of these compounds showed a clear preference for the orthosteric binding pocket with submicromolar affinity. A second compound revealed binding at a nonorthosteric binding region and showed specific biological activity on NTS1-expressing cells. A search of analogs led to further enhancement of affinity, but at the expense of activity. The identification of GPCR ligands in a cell-free assay should allow the expansion of GPCR pharmaceuticals with antagonistic or agonistic activity.